Comparative study of image quality between gold nanoparticles and iodine contrast media using mobile and general X-Ray - Said, Nooriedayu Mohd (Universiti Sains Malaysia, 2016)
To comparatively investigate the effects of Iodinated contrast media (CM) and Gold nanoparticles as potential contrast media to increase the image quality in general radiography. AuNps and Iodine were prepared in 3mMol, 5mMol, 10mMol, 15mMol, 20mMol, 30mMol and 40mMol. Those samples were exposed under digital radiography (DR) and computed radiography (CR) techniques from 50 kVp to 110kVp and 5 mAs. The regions of interests (ROIs) were drawn on the image to obtain the mean pixel value (MPV). Signal-to-Noise Ratio (SNR), Contrast-to-Noise Ratio (CNR) and Mean Pixel Contrast (MPC) then were calculated from MPV. The SNR value of AuNPs and Iodine contrast media were dependent on the tube potential used. The SNR value increase linearly with tube potential for CR and for DR the linear increase stop at 70 kVp and remain constant. The CNR value also show similar pattern for AuNPs and iodine but show significant different at higher kVps. The MPC also found to be higher in DR compared to CR. The study found that 40 mMol produce the best image quality for CR and 3 mMol is enough to obtain similar results with DR. This study indicates the potential of AuNPs as contrast agent. However, more optimization on the nanoparticles concentration and characteristic as well as the tube potential is necessary to translate the application of AuNPs into clinical practice.